666 Comparison of Minimally Invasive and Open Surgical Approaches for Intradural-Extramedullary Spine Tumors: A Systematic Review and Meta-Analysis. (April 2023) - Urooj, Faiza; Baig, Ahmer Nasir; Bajwa, Mohammad Hamza; Shamim, Shahzad M.
Abstract : INTRODUCTION: Traditionally spinal intradural-extramedullary (ID-EM) tumors have been accessed via open surgery. Removal of these tumors involves significant tissue damage, prolonged recovery, and risk of infection. More recent minimally invasive surgery (MIS) techniques aim to reduce these risks and complications while achieving similar goals of surgery as traditional approaches. METHODS: A systematic literature search was employed (PROSPERO#CRD42022302574) with searches through PubMed (MEDLINE), EBSCO, and Wiley Cochrane Library databases from conception till 9th January 2022. Cohort and case series studies with comparisons of minimally-invasive and open surgery for ID-EM spinal tumors were included; pooled sampled data were included in the random-effects (Mantel-Haenszel method) model for meta-analysis. RESULTS: Our search strategy yielded 403 total articles across these databases – after systematic review and exclusion, 13 studies were included for qualitative and quantitative analysis. On meta-analysis, minimally-invasive approaches were non-inferior to open surgery for achieving gross total resection (RR = 1.01, 95% CI 0.94 – 1.09, p = 0.78, I 2 = 0%). Intraoperative blood loss (MD = -119.18, 95% CI -157.83 - -80.52, p < 0.0001, I 2 = 89%), operative time (MD = -25.94, 95% CI -50.28 – -1.60, p = 0.04, I 2 = 91%), and length of stay (MD=-2.50, 95% CI -3.89 – -1.10, p = 0.0004, I2 = 95%) were significantly lower within cohorts undergoing MIS surgery for ID-EM spinal tumor. CONCLUSIONS: Data within the reviewed studies suggest similar rates of gross total resection within MIS and open surgery cohorts for ID-EM spinal tumors. Moreover, MIS affords shorter hospital stays, decreased blood loss, and operative time for patients. For certain patient groups, MIS spinal tumor resection can be preferred over standard surgical approaches, with preservation of function and decreasing overall surgical complications.